Social mobility and economic development - Guido Neidhöfer; Matías Ciaschi; Leonardo Gasparini; Joaquín Serrano (Journal of Economic Growth, 2023)
We explore the relationship between social mobility and economic development. First, we map the geography of intergenerational mobility in education for 52 Latin American regions, and examine its evolution over time. Then, through a new weighting procedure considering the level of participation of various cohorts in the economy in each year, we estimate the association between changes in mobility and regional economic indicators, such as income per capita, inequality, poverty, labor formality, and luminosity. Our findings show that increasing social mobility is consistently associated with economic development and growth in Latin America.
Keywords: D63; I24; J62; O15; 330; Intergenerational mobility; Equality of opportunity; Development; Growth; Latin America